Analisis Pola Komunikasi pada Pelaku Budaya Ojhung di Kecamatan Kendit Situbondo - Huzaimatul Hilalia; Siti Raudhatul Jannah (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Communication is an inseparable part of everyday life. Likewise with the hereditary beliefs that come from this Bugeman Village. Oh, his name. Ojhung is a violent activity, hitting each other between players using rattan with three strokes per player, which is then believed by the community as a means of asking for rain and rejecting reinforcements'. Through the communication carried out by the Ojhung actors, this culture has remained sustainable to this day. Based on the problems that have been described, the focus of the problem in this thesis are: 1) How does the pattern of circular communication take place between traditional leaders and Ojhung actors? 2) How does the pattern of linear communication take place between fellow Ojhung actors? 3) How does the secondary communication pattern take place between Ojhung actors and non-perpetrators? The purpose of this study is to analyze and describe the communication process that occurs in the Ojhung Culture actors in Bugeman Village through the types of communication patterns brought by several communication experts. The researcher used descriptive qualitative research. The data collection techniques used interviews, observation, and documentation. This study concludes that the relationship between culture and communication is reciprocal. Both influence each other. This shows that the people there have many ways of communicating for the sustainability of the Ojhung Culture.